2005
DOI: 10.2135/cropsci2005.0092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution to Yield Gains in the Florida Sugarcane Industry across 33 Years

Abstract: Sugarcane (Saccharum spp.) is a successful crop in the Florida Everglades Agricultural Area (EAA) that is characterized by high‐N organic and low‐fertility sandy soils, periodic freeze, and flood events. After 50 yr of breeding, the possibility of a yield plateau was investigated in the cooperative Florida sugarcane breeding program via an assessment of yield gains in the industry and an evaluation of the contribution attributed to breeding efforts. Long‐term commercial and selection trial data, covering a 33‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 12 publications
8
94
3
1
Order By: Relevance
“…This is dependent on temperature and sunlight, and would probably occur under tropical conditions. Sugarcane breeding programs have reported sugar yield gains in the order of 1% to 2% per year (Edme et al, 2005). The economic sustainability of growing energy cane in nontraditional cane growing regions will require yearly biomass yield gains of this magnitude or greater, with a goal of ensuring that the I/O ratio of 1:8 projected for tropical countries can be met and ultimately exceeded under the sub-tropical cane growing conditions of the southeastern United States.…”
Section: Production and Agronomicsmentioning
confidence: 99%
“…This is dependent on temperature and sunlight, and would probably occur under tropical conditions. Sugarcane breeding programs have reported sugar yield gains in the order of 1% to 2% per year (Edme et al, 2005). The economic sustainability of growing energy cane in nontraditional cane growing regions will require yearly biomass yield gains of this magnitude or greater, with a goal of ensuring that the I/O ratio of 1:8 projected for tropical countries can be met and ultimately exceeded under the sub-tropical cane growing conditions of the southeastern United States.…”
Section: Production and Agronomicsmentioning
confidence: 99%
“…A major goal of the Canal Point (CP) sugarcane cultivar selection program in Florida is to develop high-yielding cultivars with disease resistance and tolerance to abiotic stresses for organic (muck) and sand soils (Glaz and Kang, 2008). Edme et al (2005) reported that, for a 33-year period, about 69% of the sugar yield gain in south Florida was from genetic improvements attributable to the CP cultivar selection program, but these yield gains were mainly associated with muck rather than sand soils. Based on these findings, scientists in Florida are conducting a comprehensive review of the CP program to identify breeding and management strategies that will improve sugarcane yields for sand soils without compromising the progress being made for muck soils (Glaz and Kang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Stress symptoms of sugarcane on sand soils in Florida are generally not so extreme that they are detected visibly. However, based on the low yields and lack of genetic gain on sand soils (Edme et al, 2005), we hypothesized that physiological processes are negatively affected by abiotic stresses, especially water-deficit stress during sugarcane formative growth on the Florida sand soils. Therefore, identification of physiological and growth responses in sugarcane to water-deficit stress should aid to better understand physiological mechanisms and improve cultivar selection and field management for sand soils in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…Cane yield (TCH, Mg ha −1 ), commercial recoverable sucrose (CRS, kg sucrose Mg −1 cane), and sucrose yield (TSH, Mg ha −1 ) with disease resistance are the major agronomic traits considered in advancing sugarcane clones during the selection stages. Edmé et al [11] reported that CRS, TCH, and TSH of the Florida commercial sugarcane cultivars linearly increased by 26.0, 15.5, and 47.0%, respectively, over a 33-year period from 1968 to 2000. Underscoring the critical need for cultivar development for the Florida sugarcane industry, about 69% of the sugar yield gain in Florida was from genetic improvement attributable to the CP program [11], indicating importance of the CP program in sustaining sugarcane production in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…Edmé et al [11] reported that CRS, TCH, and TSH of the Florida commercial sugarcane cultivars linearly increased by 26.0, 15.5, and 47.0%, respectively, over a 33-year period from 1968 to 2000. Underscoring the critical need for cultivar development for the Florida sugarcane industry, about 69% of the sugar yield gain in Florida was from genetic improvement attributable to the CP program [11], indicating importance of the CP program in sustaining sugarcane production in Florida. Brown rust (Figure 1), caused by Puccinia melanocephala Syd.…”
Section: Introductionmentioning
confidence: 99%